Third-Party Perceptions of Male and Female Status: Male Physical Strength and Female Physical Attractiveness Cue High Status - Krems, Jaimie Arona; Merrie, Laureon A.; Short, Victoria; Duarte, Krystal; Rodriguez, Nina N.; French, Juliana E.; Sznycer, Daniel; Byrd-Craven, Jennifer (Frontiers in Ecology and Evolution, 2022)
Status is a universal feature of human sociality. A lesser-studied adaptive problem surrounding status is assessing who has which levels of status in a given group (e.g., identifying which people possess high status). Here, we integrate theory and methods from evolutionary social science, animal behavior, and social psychology, and we use an emotion inference paradigm to investigate what cues render people high status in the eyes of social perceivers. This paradigm relies on robust associations between status and emotion display—particularly the anger display. If a target is expected to enact (but not necessarily feel) anger, this would suggest that social perceivers view that target as higher status. By varying target attributes, we test whether those attributes are considered status cues in the eyes of social perceivers. In two well-powered, pre-registered experiments in the United States (N = 451) and India (N = 378), participants read one of eight vignettes about a male or female target—described as high or low in either physical strength or physical attractiveness (possible status cues)—who is thwarted by another person, and then reported expectations of the target’s felt and enacted anger. We find that people expected physically stronger (versus less strong) men and more (versus less) physically attractive women to enact greater anger when thwarted by a same-sex other. Strength had no significant effect on estimations of female status and attractiveness had no significant effect on estimations of male status. There were no differences in expectations of felt anger. Results suggest that people use men’s strength and women’s attractiveness as status cues. Moreover, results underscore the notion that focusing on male-typical cues of status might obscure our understanding of the female status landscape. We discuss how this paradigm might be fruitfully employed to examine and discover other unexplored cues of male and female status.